Die bittereinderstandpunt van President M.T. Steyn tydens die Anglo-Boereoorlog van 1899–1902 – "n Etiese beoordeling - Strauss, Piet J. (HTS teologiese studies, 2019)
The die-hard viewpoint of an influential figure like President M.T. Steyn of the Republic of the Orange Free State (1896–1902) led to the lengthening of the Anglo-Boer War by more than a year. The reasons for Steyn leading the Free State into this war, the reasons for his call not to surrender and the effect of the war on the Afrikaner, is discussed in this article. An ethical discussion of factors indicating a bitter end, is also on the cards. There was a strong realisation among the representatives of the Republics of the Free State and the Transvaal in 1902 that this is the end of the war.